Assessment of the training program for Versius, a new innovative robotic system for use in minimal access surgery - Fiona Haig; Jessica Butterworth; Margaux Sadry; Danielle Julian (BMJ Surgery, Interventions, & Health Technologies, 2021)
Objectives The Versius surgical system has been developed for use in robot-assisted minimal access surgery (MAS). This study aimed to evaluate the effectiveness of the Versius training program.Design A 3.5-day program following 10 hours of online didactic training. Participants were assessed during the technical training using the Global Evaluative Assessment of Robotic Skills (GEARS).Setting Dry box exercises were conducted in classrooms, and wet lab sessions simulated an operating room environment using cadaveric specimens.Participants Seventeen surgical teams participated; surgeons represented general, colorectal, obstetrics/gynecology, and urology specialties. All surgeons had previous laparoscopic MAS experience, while experience with robotics varied.Main outcomes measures Participants were scored on a five-point Likert Scale for each of six validated GEARS domains (depth perception, bimanual dexterity, efficiency, force sensitivity, autonomy, and robotic control). Additional metrics used to chart surgeon performance included: combined instrument path length; combined instrument angular path; and time taken to complete each task.Results Participants demonstrated an overall improvement in performance during the study, with a mean GEARS Score of 21.0 (SD: 1.9) in Assessment 1 increasing to 23.4 (SD: 2.9) in Validation. Greatest improvements were observed in the depth perception and robotic control domains. Greatest differences were observed when stratifying by robotic experience; those with extensive experience consistently scored higher than those with some or no experience.Conclusions The Versius training program is effective; participants were able to successfully operate the system by program completion, and more surgeons achieved intermediate-level and expert-level GEARS scores in Validation compared with Assessment 1.